APPLICATION OF ATOMIC ABSORPTION SPECTROPHOTOMETRY IN QUANTITATIVE ANALYSIS OF METALLIC CATION COMPONENT OF COMMERCIAL DRINKS - WIJAYA (NIM 10704112), HENDRA
Commercial drinks, especially those claimed to be isotonic, usually contain various metallic cations at part per million levels; accordingly the method applied for analyzing these cations should have a sensitivity appropriate to the levels of cation concentration. Atomic Absorption Spectrophotometry (AAS), a method specific for analyzing metallic cation, may have a detection limit for metallic cations at part per million levels or less. By using this method, for analyzing metallic cations of high concentration, the sample should be diluted first to make their concentrations to be in the range where the concentrations and the respective relative absorbances having a linear correlation. This AAS method has a detection limit for Na 8.1 ppm; K 0.04 ppm; Ca 0.08 ppm; Mg 0.003 ppm; and a limit quantification for Na 24.5 ppm; K 0.12 ppm; Ca 0.24 ppm; Mg 0.0098 ppm. The recovery percentages were range from 93-99% for Na, 95-105% for K, 90-109% for Ca, and 90-105% for Mg.